PEMBAGIAN WARIS SISTEM KEKERABATAN MATRILINEAL DITINJAU DARI PERSPEKTIF KITAB UNDANG-UNDANG HUKUM PERDATA - Rahmadi Rahmadi (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstractThe division of inheritance is an integral part of civil law as a whole and is the smallest part of family law which can not be separated from the sphere of religion and beliefs held. Form and inheritance law system is closely related to the shape of social and familial nature that have capital base of the system draws lineage. System of inheritance laws exist and apply in Indonesia is still plural so multi-faceted, either in the form of traditional law, Islamic law and civil law which is based on BW ( Burgelijk Wetboek ).The division of inheritance matrilineal kinship system in Minangkabau society is one system of inheritance law customary fascinating lineage of the mother which is calculated according to the mother, the brothers and sisters, mothers and relatives of both men and women and so on according to the lineage of women . Civil legal system governing the division of inheritance is also quite dominant comes together and apply to the public in the jurisdiction of Indonesia. Where the system of inheritance law has a different style and the nature of the pattern and nature of the traditional inheritance law.